The Influence of Price and Product Quality on Home Purchasing Decisions - Gayatri, Ni Putu Krishna Ananda Satya; Nayotama, A A Endra Danasura (PT. Global World Scientific, 2023)
This study examines the influence of price and product quality on home purchasing decisions. The population includes individuals or families planning to buy a house or who have purchased one in the last five years. Using purposive sampling, 36 respondents were selected based on the Slovin formula with a 5% margin of error. Data were gathered through a questionnaire employing a five-point Likert scale. Regression analysis revealed that price has a positive and significant effect on purchasing decisions (t = 13.936; p = 0.000), aligning with consumer behavior theory, which highlights price as a key factor—especially in the property sector. Similarly, product quality significantly affects home buying decisions (t = 3.021; p = 0.005), emphasizing the importance of elements such as materials, design, and facilities. The coefficient of determination (R² = 0.876) indicates that 87.6% of the variation in home purchasing decisions is explained by price and product quality, while the adjusted R² (0.868) confirms strong model reliability. These findings suggest that property developers should prioritize competitive pricing and quality improvements to align with consumer preferences and enhance market competitiveness.